Effects of General Anesthesia Plus Multimodal Analgesia on Immediate Perioperative Outcomes of Hamstring Tendon Autograft ACL Reconstruction - Brian E. Walczak, DO, PhD; Eamon D. Bernardoni, MD; Quinn Steiner, BS; Geoffrey S. Baer, MD, PhD; Melanie J. Donnelly, MD; John A. Shepler, MD (JBJS Open Access, 2023)
Background:. Anterior cruciate ligament reconstruction with hamstring tendon autograft (H-ACLR) is a standard ambulatory procedure with the potential for considerable postoperative pain. We hypothesized that general anesthesia combined with a multimodal analgesia regimen would reduce postoperative opioid use associated with H-ACLR. Methods:. This study was a single-center, surgeon-stratified, double-blinded, placebo-controlled, randomized clinical trial. The primary end point was the total postoperative opioid use during the immediate postoperative period, and secondary outcomes included postoperative knee pain, adverse events, and ambulatory discharge efficiency. Results:. One hundred and twelve subjects, 18 to 52 years of age, were randomized to placebo (57 subjects) or combination multimodal analgesia (MA) (55 subjects). The MA group required fewer opioids postoperatively (mean ± standard deviation, 9.81 ± 7.58 versus 13.88 ± 8.49 morphine milligram equivalents; p = 0.010; effect size = −0.51). Similarly, the MA group required fewer opioids within the first 24 hours postoperatively (mean ± standard deviation, 16.56 ± 10.77 versus 22.13 ± 10.66 morphine milligram equivalents; p = 0.008; effect size = −0.52). The subjects in the MA group reported lower posteromedial knee pain (median [interquartile range, IQR]: 3.0 [0.0 to 5.0] versus 4.0 [2.0 to 5.0]; p = 0.027) at 1 hour postoperatively. Nausea medication was required for 10.5% of the subjects receiving the placebo versus 14.5% of the subjects receiving MA (p = 0.577). Pruritis was reported for 17.5% of subjects receiving the placebo versus 14.5% receiving MA (p = 0.798). The median time to discharge was 177 minutes (IQR, 150.5 to 201.0 minutes) for subjects receiving placebo versus 188 minutes (IQR, 160.0 to 222.0 minutes) for those receiving MA (p = 0.271). Conclusions:. A combination of general anesthesia and local, regional, oral, and intravenous multimodal analgesia appears to reduce postoperative opioid requirements after H-ACLR compared with placebo. Adding preoperative patient education and focusing on donor-site analgesia may maximize perioperative outcomes. Level of Evidence:. Therapeutic Level I. See Instructions for Authors for a complete description of levels of evidence.